Glaucoma Literacy in a Portuguese Population - Pestana Aguiar Catarina; Alves Ambrósio João; Lopes Cardoso Isabel; Amorim Manuela; Chibante Pedro João; Jesus Jeniffer (Journal of Ophthalmic Science, 2024)
Studies show that individuals with limited health literacy skills experience worse health outcomes in a multitude of chronic diseases including glaucoma. These patients have poorer compliance, worse disease understanding and greater disease progression. The main purpose of our study was to evaluate the knowledge about glaucoma basic concepts in patients with this disease. A 24 question survey was given to patients followed by the glaucoma department, by phone or in person. Epidemiological data and personal therapeutic regimens were collected as well as data concerning the pathophysiology, treatment and prognosis of the disease. Survey responses were obtained from 79 patients with a mean age of 72 years old. Most of the patients had a low education level. The majority of patients could not enumerate glaucoma risk factors (74.5%), their glaucoma type (94.9%) or the best glaucoma definition (57%). However, they were able to relate the disease to a high IOP (75.9%) and the possibility of it leading to blindness (96.2%). We believe that patients, when observed in their glaucoma appointments, tend to retain information related to the prognosis and consequences of the disease and not focus on the understanding of its pathophysiology, causes and mechanisms, which may reflect their concern about their own future. However, this may lead to some misconceptions about the definition of glaucoma and specially about what can cause this disease. Some investment should be done to improve health literacy in the glaucoma population, with appropriate language and handed material.
Keywords: Open angle Glaucoma